Motywy tatuowania się osób z niepełnosprawnością ruchową a ich dobrostan psychiczny = Motives for tattooing people with physical disabilities and their mental well-being - Wojciechowska, Ludwika; Kasperek, Dorota Katarzyna; Olszewska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the study was to find out the relationship between the motives for tattooing and emotional, personality and social well-being in groups of people with and without physical disabilities. A positive relationship between the three types of tattooing motives and the three dimensions of mental well-being was expected both in the group of people with physical disabilities and in the group without disabilities. The second objective was to find out the differences between the study groups in terms of the intensity of tattooing motives.
Keywords: motywy robienia tatuaży; dobre samopoczucie psychiczne; osoby z niepełnosprawnością fizyczną; motives for tattooing; mental well-being; people with physical disabilities